2023
DOI: 10.3390/curroncol30030236
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Anastomotic Leakage Following Colorectal Cancer Surgery: Where Are We and Where Are We Going?

Abstract: Anastomotic leakage (AL) remains one of the most severe complications following colorectal cancer (CRC) surgery. Indeed, leaks that may occur after any type of intestinal anastomosis are commonly associated with a higher reoperation rate and an increased risk of postoperative morbidity and mortality. At first, our review aims to identify specific preoperative, intraoperative and perioperative factors that eventually lead to the development of anastomotic dehiscence based on the current literature. We will also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 224 publications
(328 reference statements)
0
2
0
Order By: Relevance
“…For instance, anastomotic leakage after colorectal surgery can lead to the serious complications of abdominal and pelvic sepsis, wound infections, fecal incontinence, and tumor recurrence, as well as postoperative death [9][10][11]. The overall incidence of anastomotic leakage after colorectal cancer resection is reported to be 2-19% [12][13][14]. In general, the bursting pressures of the gastrointestinal anastomosis sites are significantly decreased during the first three days, and most leakages after colorectal surgery occur within the first week [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, anastomotic leakage after colorectal surgery can lead to the serious complications of abdominal and pelvic sepsis, wound infections, fecal incontinence, and tumor recurrence, as well as postoperative death [9][10][11]. The overall incidence of anastomotic leakage after colorectal cancer resection is reported to be 2-19% [12][13][14]. In general, the bursting pressures of the gastrointestinal anastomosis sites are significantly decreased during the first three days, and most leakages after colorectal surgery occur within the first week [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative anastomotic leaks following oncological right hemicolectomy pose serious complications associated with increased morbidity and mortality [ 5 ]. An international multicenter study reported an overall ileocolic anastomotic leak rate of 7.4%, with 30-day morbidity and mortality rates of 38% and 10.6%, respectively [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that patients receiving neoadjuvant chemoradiotherapy also pose a risk of anastomotic leakage. The rate of anastomotic leakage varied greatly in published series, reported between 2% and 19%, but in reference centers and with experienced teams, it is 2-7% [ 14 ]. Although we have a robust anastomotic leakage rate, our study revealed that we should strive to reduce our overall complication rate after colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 99%